HUBUNGAAN KOMUNIKASI DENGAN MINAT KEMBALI PEMANFAATAN PELAYANAN DI RUMAH SAKIT - -, Heriyati (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2021)
Abstract: Return interest is part of the form of customer satisfaction after receiving service. Based on the number of outpatient visits at Majene Hospital, it is known that the number of visits is fluctuating. The aim of this study was to determine the relationship between communication and interest in returning visits to the outpatient service at Majene Hospital. This research is a quantitative study with a cross sectional study design. The sampling method was purposive sampling with a total sample size of 394 people. Based on the results, it was found that there was a relationship between communication and the interest in patient return visits with a value of p = 0.000 (p <0.05). The conclusion of this study, there is a significant relationship between communication with the interest in returning patients to the outpatient installation of Majene Hospital. It is hoped that the hospital will continue to pay attention to and implement effective communication so that the quality of health services increases so that patients and the public are interested in using the service facilities in the outpatient installation of Majene Hospital.